Eco-efficient ternary mixtures incorporating fly ash and metakaolin - Reis, Rui (2011)
With the growing awareness of environmental problems, particularly with regard to energy efficiency and greenhouse gas emissions, the construction and the cement industry has had a prominent place, the latter being responsible for about 7% of CO2 emissions into the atmosphere. Knowing that cement production contributes about one tone of CO2 for every tone produced, it remains paradoxical that concrete, the product most consumed by humans, exceeded only by water, cannot find a credible replacement material for Portland cement, more efficient and greener. Considering the available technological solutions, involving energy efficiency of cement intensive production or the demand for alternative fuels for cement manufacture, a simpler solution might be the rationalization of resources by cement replacement by alternative materials. There is already a kind of concrete (high volume fly ash concrete) with very limited applications until nowadays but with intrinsically strong environmental advantages. However, the reduced early strength of this type of concrete is a limiting factor for his widespread usage. In this context, a study was developed in mortars with ternary mixtures where significant volumes of cement were replaced by fly ash, and also, simultaneously, for another addition functioning as a corrector of performance, the metakaolin. In this paper, one present the main advantages and drawbacks of the simultaneous use of these two mineral additions which synergy may cause very interesting performance characteristics even with high volumes of cement replacement. These ternary mixtures show very promising performances, allowing large volumes of cement replacement, maintaining or improving both mechanical and durability characteristics. These binders could be a viable solution for obtaining an eco-efficient enhanced performance concrete for widespread usage in construction as an alternative to conventional concrete.